2012
DOI: 10.1017/s1355617712000951
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Semantic and Episodic Memory BOLD fMRI Activation in Predicting Cognitive Decline in Older Adults

Abstract: Previous studies suggest that task-activated fMRI can predict future cognitive decline among healthy older adults. The present fMRI study examined the relative sensitivity of semantic memory (SM) versus episodic memory (EM) activation tasks for predicting cognitive decline. Seventy-eight cognitively intact elders underwent neuropsychological testing at entry and after an 18-month interval, with participants classified as cognitively “Stable” or “Declining” based on ≥1.0 SD decline in performance. Baseline fMRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Removing incorrect trials does not entirely correct the problem because the resulting brain maps are generated from a sparse number of correct trials in individuals performing near chance. Moreover, the BOLD signals that result from greater task difficulty or effort in the poor performing group will be inseparable from activation related to memory retrieval-related processes, thus confounding any sound interpretation of the activation maps (Hantke et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Removing incorrect trials does not entirely correct the problem because the resulting brain maps are generated from a sparse number of correct trials in individuals performing near chance. Moreover, the BOLD signals that result from greater task difficulty or effort in the poor performing group will be inseparable from activation related to memory retrieval-related processes, thus confounding any sound interpretation of the activation maps (Hantke et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Although there are multiple hereditary factors associated with AD, the apolipoprotein-E (APOE) ε4 allele is a well-recognized, important risk factor for AD that is also associated with familial clustering (e.g., Saunders et al, 1993aSaunders et al, , 1993b. Furthermore, its presence has been associated with differential brain activity patterns, including in the frontal lobes, in studies with cognitively intact elders (e.g., Hantke et al, 2013;Seidenberg et al, 2013;Smith et al, 2014) and the literature as a whole supports a robust negative effect of APOE ε4 on multiple domains of cognition in healthy elders, including executive functioning (Wisdom, Callahan, & Hawkins, 2011).…”
Section: Neuropsychologymentioning
confidence: 99%
“…Rather, our definition of cognitive decline was purposely liberal in order to examine elders who are in the very early stages of cognitive decline and exhibit subtle but meaningful changes in cognitive performance. Even though the decline may not be at a clinically significant level, our previous work, using the same criteria and follow-up period as the current study, has shown that declining elders have smaller hippocampal volumes at baseline, differential patterns of fMRI activation in response to semantic and episodic memory tasks at baseline, and are more likely to carry the APOE ε4 allele (Hantke et al, 2013; Seidenberg et al, 2013; Woodard et al, 2010; Woodard et al, 2012). The current work serves to add to this literature by demonstrating that IIV can also serve as a prognostic indicator of future cognitive decline.…”
Section: Discussionmentioning
confidence: 58%